Channel electron bubbles in low-temperature helium gas - Monarkha, Yu.P. (Физика низких температур, 2018)
Self-localization of electrons caused by their interaction with helium vapor atoms in quasi-one-dimensional conducting channels over liquid helium is theoretically studied. We have shown that channel electron bubbles of a large size can exist at temperatures which are substantially lower than the critical temperature reported previously for electron bubbles of three-dimensional and two-dimensional electron systems. The transition from a large-size bubble to a small-size bubble is shown to be discontinuous, and a sort of bistability involving metastable states is described. The analysis given explains a sharp decrease of electron mobility in quasi-one-dimensional channels on liquid helium observed at T  2,5 К.